Method for treating organic gas pollution through catalytic ozonation

By using the medium entropy spinel oxide catalyst CuxMn1-xFe2O4, the synergistic action of Fe, Mn and Cu is used to promote the bridge adsorption activation of ozone, solving the existing problem of low efficiency of catalytic ozone oxidation reaction, achieving efficient removal of organic gas pollution and good catalyst stability.

CN119524615APending Publication Date: 2025-02-28SUN YAT SEN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411952279.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The utilization efficiency of existing catalytic ozone oxidation reactions is low, and the catalyst is prone to deactivate, which affects the catalytic effect. Especially when dealing with organic gas pollution, it is difficult to achieve efficient removal.

Method used

The medium-entropy spinel oxide catalyst CuxMn1-xFe2O4 is used to form A-O-B bonds and Fe-O-Mn covalent bonds through the synergistic action of Fe, Mn and Cu, which promotes the bridge adsorption and activation of ozone and generates highly reactive surface atomic and molecular oxygen.

Benefits of technology

The efficiency of catalytic ozone oxidation reaction is significantly improved, the ability to remove organic gases is enhanced, and the catalyst has long-term and stable catalytic performance, which is suitable for applications in the field of air pollution control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524615A_ABST
    Figure CN119524615A_ABST
Patent Text Reader

Abstract

The invention provides a method for treating organic gas pollution through catalytic ozonation, and belongs to the field of air pollution treatment. According to the method, the catalyst is placed in a continuous flow microreactor, under the condition that a certain flow speed of ozone is set, the organic gas is subjected to catalytic degradation removal, the catalyst is a medium-entropy spinel oxide catalyst, namely CuxMn1-xFe2O4, and x is equal to 0-0.75. Compared with an existing ozone catalysis technology, the catalytic efficiency is high, stable catalytic removal of the sulfur-containing organic volatile gas is achieved, and a new technical scheme is provided for green and efficient treatment of the sulfur-containing organic volatile gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of air pollution control, and more specifically, to a method for treating organic gas pollution by catalytic ozone oxidation. Background Art

[0002] The current organic gas pollution in the environment is very serious, posing a significant threat to human health and ecosystems. Volatile organic compounds (VOCs) are one of the important pollutants causing atmospheric haze and ozone pollution. Among them, sulfur-containing volatile organic gases (S-VOCs) are a class of pollutants that are widely present in industrial emissions and the environment. They not only pollute the environment, but also pose a threat to human health. These gases include hydrogen sulfide, mercaptans, etc., most of which are toxic, and some have been confirmed to be carcinogens. S-VOCs are difficult to biodegrade, easily become part of the environment, and enter organisms through the food chain, affecting the physiological functions of organisms. They are also the main source of ozone layer depletion and photochemical pollution. At present, the technologies for controlling S-VOCs include traditional adsorption, absorption, and incineration technologies, as well as emerging methods such as membrane separation, catalytic combustion, and biological purification. It has become particularly important to monitor and control the emission of S-VOCs to reduce its impact on the environment and health. In indoor environments, household cleaning products are also an important source of S-VOCs. These gases produce secondary pollutants through gas-phase oxidation reactions, further affecting indoor air quality.

[0003] As a strong oxidant, ozone has been widely used in many fields such as water treatment, air pollution control, and industrial waste gas purification. Ozone has catalytic decomposition and strong oxidizing properties, and can effectively degrade organic pollutants and disinfect and sterilize. Therefore, it has important application prospects in environmental protection. However, catalytic ozone oxidation reactions face some challenges in practical applications. One of them is that the utilization efficiency of ozone is low and the catalyst is easily deactivated, which affects its catalytic effect. Traditional catalytic ozone oxidation reactions usually adopt linear adsorption. However, in linear adsorption, the interaction between ozone molecules and adsorption sites on the catalyst surface is relatively weak, resulting in low ozone activation efficiency, thereby limiting the catalytic performance of the reaction. Therefore, how to improve the activation efficiency of ozone has always been a technical problem in the field of catalytic ozone oxidation. Transition metal spinel oxides (AB2O4), such as MnFe2O4, are considered to be potential catalytic ozone oxidation catalysts. This type of catalyst has abundant resources, excellent chemical stability and adjustable structural characteristics. The atoms at the A and B positions in spinel oxides occupy tetrahedral and octahedral sites respectively, and the atoms at the A and B positions are connected to the same oxygen atom through corner sharing to form an AOB bond. The synergistic effect of multiple metals in spinel effectively improves the catalytic efficiency of multi-metal spinel.

[0004] The prior art discloses an iron-cobalt doped ozone activation catalyst Fe-CoO x The study shows that the synergistic effect of Fe and Co in the bimetallic oxide can effectively increase the ozone oxidation rate, improve the ozone utilization rate, and can be reused. However, the ozone activation efficiency is still restricted by the surface properties of the catalyst and the reaction conditions. The prior art also provides a method for removing organic matter from water by catalyzing ozone with a spinel ferrite catalyst, but the method of use is restricted by water bodies and cannot broaden its application in treating organic gases.

[0005] Therefore, developing a method for treating organic gas pollution by catalytic ozone oxidation with high catalytic efficiency and stable catalytic removal of organic gas pollution has important research significance and application value. Summary of the invention

[0006] The present invention aims to overcome the deficiencies of the prior art and provide a method for treating organic gas pollution by catalytic ozone oxidation, which achieves high catalytic efficiency and stable catalytic removal of organic gas pollution.

[0007] Therefore, the primary object of the present invention is to provide a method for treating organic gas pollution by catalytic ozone oxidation.

[0008] Another object of the present invention is to provide application of the above method in the field of air pollution control.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] The present invention provides a method for treating organic gas pollution by catalytic ozone oxidation, comprising the following steps:

[0011] The catalyst was placed in a continuous flow microreactor with an ozone flow rate of 3 to 30 mL / min and organic gas introduced;

[0012] Wherein, the catalyst is a medium entropy spinel oxide catalyst, Cu x Mn 1-x Fe2O4, x = 0 to 0.75;

[0013] Organic gas is sulfur-containing organic volatile gas.

[0014] The present invention mainly uses a medium entropy spinel oxide catalyst in a continuous flow microreactor, including three metal elements of Fe, Mn and Cu, which occupy octahedral and tetrahedral positions in the spinel structure, respectively. Among them, the metal in the tetrahedron and the metal in the octahedron are connected by the same oxygen atom to form an AOB bond, thereby promoting the redox cycle between the metals, and producing a synergistic effect to enhance the catalytic activity. The present invention designs catalysts based on the covalent competition theory, and combines theoretical calculations to obtain multi-metal spinel oxides with different metal ratios. The catalyst regulates the overlap of the electron cloud between the metal and the oxygen atom through the covalent competition of the AOB bond, thereby promoting electron transfer and improving the catalytic performance. In addition, the multi-metal spinel oxide described in the present invention further enhances its catalytic performance by promoting the bridging adsorption of ozone. Multiple metal elements play different roles in the catalytic process through unique electronic structures and redox properties. In particular, the corner-shared Fe and Mn enhance the covalent competition between Fe-O-Mn by forming a Fe-O-Mn covalent bond, thereby improving the bridge adsorption activation of O3. O3 molecules are activated on the catalyst surface through bridge adsorption to generate highly reactive surface atomic oxygen (*O) and surface molecular oxygen (*O2). At the same time, the porous sponge structure of the catalyst facilitates full contact between pollutants and active species, further accelerating the removal of pollutants. In the reaction system of catalytic ozonation to remove sulfur-containing volatile organic gases, the Fe-O-Mn covalent competition effect enriches the Fe and Mn sites with electrons, promotes the bridge adsorption activation of ozone, and generates strong oxidizing active species such as surface atomic oxygen and molecular oxygen. At the same time, the Cu site, as the main adsorption site for sulfur-containing organic gases, effectively separates the positions of ozone activation and pollutant adsorption, thereby improving the sulfur resistance of the catalyst and effectively preventing sulfur poisoning of the catalyst. In addition, the porous structure of the catalyst significantly increases the exposure of active sites, enhances the contact between pollutants and active species, and further improves the catalytic effect.

[0015] Controlling the ozone flow rate is mainly to adjust the ozone concentration in the reaction system. When the ozone flow rate is low, the activated active oxygen species are few, which is not conducive to the removal of organic matter; when the ozone flow rate is high, it will cause ozone excess and increase the application cost. In the present invention, by optimizing the spinel bridge adsorption of ozone, the efficient utilization and activation of ozone is achieved, and the efficient removal of organic pollutants can be achieved at a suitable ozone concentration.

[0016] In the specific implementation, the present invention adopts three metal elements, Fe, Mn and Cu. These transition metals not only have good catalytic effects, but also are low-priced, easy to obtain, and have abundant reserves in nature, which facilitates industrial production.

[0017] Preferably, the sulfur-containing organic volatile gas is selected from one or more of methyl mercaptan, ethyl mercaptan, methyl sulfide, dimethyl disulfide or carbon sulfide.

[0018] Preferably, the ozone flow rate is 5 to 15 mL / min.

[0019] More preferably, the ozone flow rate is 10 mL / min.

[0020] Preferably, the continuous flow microreactor is used in the prior art, preferably a continuous flow fixed quartz microreactor.

[0021] Preferably, the inlet humidity of the continuous flow microreactor is 0% to 70%.

[0022] More preferably, the inlet humidity of the continuous flow microreactor is 20% to 70%.

[0023] Specifically, the ozone is generated by an ozone generator, and the flow rate is controlled by a mass flow meter.

[0024] Preferably, the concentration of ozone is 500-1000 ppm.

[0025] Preferably, the sulfur-containing organic volatile gas is used at a concentration of 40 to 60 ppm.

[0026] Specifically, the sulfur-containing volatile organic gas uses a corresponding standard gas as a simulated pollutant, and the concentration of the sulfur-containing organic volatile gas after dilution is 40 to 60 ppm.

[0027] Preferably, the catalyst is Cu x Mn 1-x Fe2O4, x=0, 0.25, 0.5, 0.75.

[0028] Specifically, MnFe2O4, Cu 0.25 Mn 0.75 Fe2O4、Cu 0.5 Mn 0.5 Fe2O4 or Cu 0.75 Mn 0.75 One or more of Fe2O4.

[0029] Preferably, the method for preparing the catalyst comprises the following steps:

[0030] S1. Mix one or more metal salts of Cu, Fe or Mn and citric acid in a predetermined ratio and grind evenly;

[0031] S2. The mixture is placed in an air atmosphere and calcined at 300-500° C. for 1.5-2.5 h to obtain a medium-entropy spinel oxide catalyst.

[0032] More preferably, the calcination temperature is 350-450°C, more preferably 400°C.

[0033] Preferably, the metal salt is a nitric acid or acetate metal salt.

[0034] Specifically, the metal salt is one or more of ferric nitrate, copper acetate or manganese acetate.

[0035] Preferably, the mass ratio of the metal salt to citric acid is 1:2 to 1:3.

[0036] Preferably, the flow rate of the air is selected with reference to the prior art.

[0037] The application of the above-mentioned method for treating organic gas pollution by catalytic ozone oxidation in the field of air pollution control is also within the protection scope of the present invention.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The present invention provides a method for treating organic gas pollution by catalytic ozone oxidation, which uses a continuous flow microreactor to catalyze ozone reaction under the action of a medium entropy spinel oxide catalyst to remove sulfur-containing organic volatile gases;

[0040] 2. The medium entropy spinel oxide catalyst of the present invention exhibits excellent pollutant removal ability in the field of air pollution control, especially in the process of efficiently removing sulfur-containing volatile organic gases. The catalyst can efficiently remove sulfur-containing gases and realize their mineralization, effectively controlling the emission of sulfur-containing volatile organic gases. In addition, the preparation method of the multi-metal spinel oxide of the present invention is simple, low-cost, easy to mass produce, and has long-term stable catalytic performance. As an environmentally friendly material, the catalyst meets the requirements of low-carbon environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The Cu prepared in Examples 1 to 4 x Mn 1-x Covalent competition calculation results of Fe2O4 catalyst;

[0042] Figure 2 The Cu prepared in Examples 1 to 4 x Mn 1-x Calculation results of charge distribution of Fe2O4 catalyst;

[0043] Figure 3 The Cu prepared in Examples 1 to 4 x Mn 1-x Scanning electron microscope (SEM) image of Fe2O4 catalyst;

[0044] Figure 4 The Cu prepared in Examples 1 to 4 x Mn 1-xX-ray diffraction (XRD) pattern of Fe2O4 catalyst;

[0045] Figure 5 The Cu prepared in Examples 1 to 4 x Mn 1-x Raman spectrum of Fe2O4 catalyst;

[0046] Figure 6 The Cu prepared in Example 1 0.25 Mn 0.75 In situ Raman spectrum of Fe2O4 catalyst;

[0047] Figure 7 The Cu prepared in Example 1 0.25 Mn 0.75 Adsorption data of methyl mercaptan and ozone on Fe2O4 catalyst. DETAILED DESCRIPTION

[0048] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0049] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0050] Example 1 A method for treating organic gas pollution by catalytic ozone oxidation - Cu 0.25 Mn 0.75 Fe2O4 catalyst

[0051] S1. Grind 3.15 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.1 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) and 0.368 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0052] S2. The mixture was placed in a 100 mL ceramic crucible and heated in a muffle furnace at 2 °C min -1 The mixture was heated to 400°C at a rate of 100 °C and maintained for 2 h.

[0053] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.25 Mn 0.75 Fe2O4 catalyst.

[0054] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0055] Take 3 mg of the catalyst of Example 1, place it in the middle of the reactor and fix it with cotton. The humidity of the gas at the reactor inlet is controlled by a humidity generator. Use an ozone generator to generate O3 (500 ppm), and use a mass flowmeter to control the flow rate of O3 at 10 mL min -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 40% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0056] Example 2 A method for treating organic gas pollution by catalytic ozone oxidation - MnFe2O4 catalyst

[0057] S1. Grind 3.15 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), and 0.49 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0058] S2. The mixture was placed in a 100 mL ceramic crucible and heated in a muffle furnace at 2 °C min -1 The mixture was heated to 400°C at a rate of 100 °C and maintained for 2 h.

[0059] After the calcination is completed, the material is taken out after being cooled to room temperature to obtain a MnFe2O4 catalyst.

[0060] The catalyst in Example 2 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0061] Take 3 mg of the catalyst of Example 2 and use the same testing method as Example 2.

[0062] Example 3 A method for treating organic gas pollution by catalytic ozone oxidation

[0063] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Cu, specifically represented by Cu 0.5 Mn 0.5 Fe2O4.

[0064] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0065] S1. Grind 3.15 g of citric acid monohydrate, 1.616 g of ferric nitrate nonahydrate, 0.2 g of copper acetate monohydrate and 0.245 g of manganese acetate tetrahydrate in a mortar until well mixed;

[0066] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 400°C at a rate of 100 °C and maintained for 2 h.

[0067] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.5 Mn 0.5 Fe2O4 catalyst.

[0068] The catalyst in Example 3 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0069] 3 mg of the catalyst of Example 3 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0070] Example 4 A method for treating organic gas pollution by catalytic ozone oxidation

[0071] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Cu, specifically represented by Cu 0.75 Mn 0.25 Fe2O4.

[0072] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0073] S1. Grind 3.15 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.3 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) and 0.123 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0074] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 400°C at a rate of 100 °C and maintained for 2 h.

[0075] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.75 Mn 0.25 Fe2O4 catalyst.

[0076] The catalyst in Example 4 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0077] 3 mg of the catalyst of Example 4 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0078] Example 5 A method for treating organic gas pollution by catalytic ozone oxidation

[0079] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0080] 3 mg of the catalyst of Example 1 was placed in the middle of the reactor and fixed with cotton. The humidity of the gas at the reactor inlet was controlled by a humidity generator. O3 (500 ppm) was generated using an ozone generator, and the flow rate of O3 was controlled at 10 mL min using a mass flow meter. -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 0% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0081] Example 6 A method for treating organic gas pollution by catalytic ozone oxidation

[0082] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0083] 3 mg of the catalyst of Example 1 was placed in the middle of the reactor and fixed with cotton. The humidity of the gas at the reactor inlet was controlled by a humidity generator. O3 (500 ppm) was generated using an ozone generator, and the flow rate of O3 was controlled at 10 mL min using a mass flow meter. -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 20% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g-1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0084] Example 7 A method for treating organic gas pollution by catalytic ozone oxidation

[0085] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0086] 3 mg of the catalyst of Example 1 was placed in the middle of the reactor and fixed with cotton. The humidity of the gas at the reactor inlet was controlled by a humidity generator. O3 (500 ppm) was generated using an ozone generator, and the flow rate of O3 was controlled at 10 mL min using a mass flow meter. -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 70% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0087] Example 8 A method for treating organic gas pollution by catalytic ozone oxidation

[0088] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0089] 1 mg of the catalyst of Example 1 was placed in the middle of the reactor and fixed with cotton. The humidity of the reactor inlet gas was controlled by a humidity generator. O3 (500 ppm) was generated using an ozone generator, and the flow rate of O3 was controlled at 10 mL min using a mass flow meter. -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 40% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0090] Example 9 A method for treating organic gas pollution by catalytic ozone oxidation

[0091] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0092] 5 mg of the catalyst of Example 1 was placed in the middle of the reactor and fixed with cotton. The humidity of the gas at the reactor inlet was controlled by a humidity generator. O3 (500 ppm) was generated using an ozone generator, and the flow rate of O3 was controlled at 10 mL min using a mass flow meter. -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 40% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0093] Example 10 A method for treating organic gas pollution by catalytic ozone oxidation

[0094] The catalyst in Example 1 is applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation is as follows:

[0095] 30 mg of the catalyst of Example 1 was placed in the middle of the reactor and fixed with cotton. The humidity of the gas at the reactor inlet was controlled by a humidity generator. O3 (500 ppm) was generated using an ozone generator, and the flow rate of O3 was controlled at 10 mL min using a mass flow meter. -1 1000ppm of CH3SH was diluted with air to keep the CH3SH concentration at the reactor inlet at 40ppm, and the relative humidity of the system was controlled to 40% by adjusting the ratio of dry air and humid air. The total flow rate of the mixed gas in the system was controlled at 100mL min using a mass flow controller. -1 , equivalent to an airspeed of 200 L·h -1 ·g -1The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 24 hours. The catalytic efficiency results are shown in Table 1.

[0096] Example 11 A method for treating organic gas pollution by catalytic ozone oxidation

[0097] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Cu, specifically represented by Cu 0.25 Mn 0.75 Fe2O4.

[0098] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0099] S1. Grind 1.58 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.1 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) and 0.368 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0100] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 400°C at a rate of 100 °C and maintained for 2 h.

[0101] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.25 Mn 0.75 Fe2O4 catalyst.

[0102] The catalyst in Example 11 was applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation was as follows:

[0103] 3 mg of the catalyst of Example 11 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0104] Example 12 A method for treating organic gas pollution by catalytic ozone oxidation

[0105] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Cu, specifically represented by Cu 0.25 Mn 0.75 Fe2O4.

[0106] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0107] S1. Grind 6.30 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.1 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) and 0.368 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0108] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 400°C at a rate of 100 °C and maintained for 2 h.

[0109] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.25 Mn 0.75 Fe2O4 catalyst.

[0110] The catalyst in Example 12 was applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation was as follows:

[0111] 3 mg of the catalyst of Example 12 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0112] Example 13 A method for treating organic gas pollution by catalytic ozone oxidation

[0113] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Cu, specifically represented by Cu 0.25 Mn 0.75 Fe2O4.

[0114] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0115] S1. Grind 3.15 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.1 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) and 0.368 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0116] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 300°C at a rate of 100 °C and maintained for 2 h.

[0117] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.25 Mn 0.75 Fe2O4 catalyst.

[0118] The catalyst in Example 13 was applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation was as follows:

[0119] 3 mg of the catalyst of Example 13 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0120] Example 14 A method for treating organic gas pollution by catalytic ozone oxidation

[0121] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Cu, specifically represented by Cu 0.25 Mn 0.75 Fe2O4.

[0122] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0123] S1. Grind 3.15 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.1 g of copper acetate monohydrate (Cu(CH3COO)2·H2O) and 0.368 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0124] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 500°C at a rate of 100 °C and maintained for 2 h.

[0125] After calcination, the material was taken out after cooling to room temperature to obtain Cu 0.25 Mn 0.75 Fe2O4 catalyst.

[0126] The catalyst in Example 14 was applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation was as follows:

[0127] 3 mg of the catalyst of Example 14 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0128] Example 15 A method for treating organic gas pollution by catalytic ozone oxidation

[0129] The experimental method is the same as that of Example 1, except that the ozone flow rate is 3 mL / min.

[0130] Example 16 A method for treating organic gas pollution by catalytic ozone oxidation

[0131] The experimental method is the same as that of Example 1, except that the ozone flow rate is 30 mL / min.

[0132] Comparative Example 1 A method for treating organic gas pollution by catalytic ozone oxidation

[0133] The catalyst in Example 1 is applied to pollutant removal, and the specific operation is as follows:

[0134] Take 3 mg of the catalyst of Example 1, place it in the middle of the reactor and fix it with cotton. The humidity of the gas at the reactor inlet is controlled by a humidity generator. Use air instead of ozone, dilute 1000 ppm of CH3SH (methyl mercaptan) with air, keep the CH3SH concentration at the reactor inlet at 40 ppm, and then control the relative humidity of the system to 40% by adjusting the ratio of dry air and moist air. Use a mass flow controller to control the total flow of the mixed gas in the system at 100 mL min -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0135] Comparative Example 2 A method for treating organic gas pollution by catalytic ozone oxidation

[0136] The catalyst in Example 1 is applied to pollutant removal, and the specific operation is as follows:

[0137] Take 3 mg of the catalyst of Example 1, place it in the middle of the reactor, and fix it with cotton. The humidity of the gas at the reactor inlet is controlled by a humidity generator. Use nitrogen instead of ozone, dilute 1000 ppm of CH3SH with nitrogen, keep the CH3SH concentration at the reactor inlet at 40 ppm, and then control the humidity of the system to 40% by adjusting the ratio of dry nitrogen and wet nitrogen. Use a mass flow controller to control the total flow of the mixed gas in the system at 100 mL min -1 , which is equivalent to an airspeed of 2000 L·h -1 ·g -1 The CH3SH sensor was used to monitor the concentration of methyl mercaptan. The concentration at the inlet was C0 and the concentration at the outlet was C. The catalytic efficiency was expressed by the degradation rate of methyl mercaptan (1-C / C0). The degradation rate was tested for 1 h. The catalytic efficiency results are shown in Table 1.

[0138] Comparative Example 3 A method for treating organic gas pollution by catalytic ozone oxidation

[0139] A common commercial MnO2 catalyst purchased from Aladdin Company.

[0140] The catalyst in Comparative Example 3 is applied to pollutant removal, and the specific operation is as follows:

[0141] 3 mg of the catalyst of Comparative Example 3 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0142] Comparative Example 4: A method for treating organic gas pollution by catalytic ozone oxidation

[0143] A common commercial MnFe2O4 catalyst was purchased from MacLean Company.

[0144] The catalyst in Comparative Example 4 was applied to pollutant removal, and the specific operation was as follows:

[0145] 3 mg of the catalyst of Comparative Example 4 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0146] Comparative Example 5: A method for treating organic gas pollution by catalytic ozone oxidation

[0147] A multi-metal spinel oxide catalyst, comprising three metal elements, Fe, Mn and Co, specifically represented by Co 0.25 Mn 0.75 Fe2O4.

[0148] The preparation method of the multi-metal spinel oxide catalyst comprises the following steps:

[0149] S1. Grind 3.15 g of citric acid monohydrate (C6H8O7·H2O, CA), 1.616 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.146 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 0.368 g of manganese acetate tetrahydrate (Mn(CH3COO)2·4H2O) in a mortar until well mixed;

[0150] S2. Place the mixture in a 100 ml ceramic crucible and heat it in a muffle furnace at 2 °C min -1 The mixture was heated to 500°C at a rate of 100 °C and maintained for 2 h.

[0151] After calcination, the material was taken out after cooling to room temperature to obtain Co 0.25 Mn 0.75 Fe2O4 catalyst.

[0152] The catalyst in Comparative Example 5 was applied to catalytic ozone oxidation of methyl mercaptan, and the specific operation was as follows:

[0153] 3 mg of the catalyst of Comparative Example 5 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0154] Comparative Example 6 A method for treating organic gas pollution by catalytic ozone oxidation

[0155] After stirring egg white at room temperature for 30 minutes, a uniform egg white solution is obtained; the nitrate of the metal element is weighed according to the atomic number ratio of the metal element in the spinel ferrite molecular formula, wherein the mass volume ratio of ferric nitrate to the egg white solution is 0.2g:1mL, the metal nitrate is added to the obtained egg white solution, and then placed in an 80°C water bath and stirred for 2 hours to obtain a mixture; the obtained mixture is calcined at 500°C for 6 hours to obtain a product; the obtained product is cooled to room temperature with an ice-water mixture, and then dried in an oven at a temperature of 50°C for 3 hours, and then ground to obtain a catalyst for ozone oxidation and decomposition of organic pollutants in water; the spinel ferrite molecular formula is MnFe2O4.

[0156] 3 mg of the catalyst of Comparative Example 6 was placed in the middle of the reactor for reaction. The specific test method was the same as that of Example 1, and the degradation rate was tested for 1 hour. The catalytic efficiency results are shown in Table 1.

[0157] Comparative Example 7 A method for treating organic gas pollution by catalytic ozone oxidation

[0158] The experimental method is the same as that of Example 1, except that the ozone flow rate is 2 mL / min.

[0159] Comparative Example 8 A method for treating organic gas pollution by catalytic ozone oxidation

[0160] The experimental method is the same as that of Example 1, except that the ozone flow rate is 35 mL / min.

[0161] Results

[0162] 1. Density functional theory calculations

[0163] Density functional theory calculations were performed on the materials of Examples 1 to 4 to calculate their covalent competition. The calculation results are as follows: Figure 1 As shown in Figure 2, the introduction of Cu significantly changed the TM-O covalency, thereby affecting the Fe-O-Mn / Cu covalent competition. Specifically, compared with MnFe2O4 in Example 2, the introduction of Cu significantly enhanced the Cu in Example 1. 0.25 Mn 0.75 The TM-O covalency of Fe2O4 further strengthens the Fe-O-Mn / Cu covalent competition. As the Cu doping amount increases, the Max TM-O (Fe-O, Mn-O, Cu-O) covalency gradually decreases, indicating that the covalent competition gradually weakens, and the order is Cu 0.25Mn 0.75 Fe2O4 (Example 1) > Cu 0.5 Mn 0.5 Fe2O4 (Example 3) > Cu 0.75 Mn 0.25 Fe2O4 (Example 4). Therefore, Cu x Mn 1-x The relationship between the covalent competition of Fe2O4 and the amount of Cu doping can be described by a volcano curve, where Cu 0.25 Mn 0.75 Fe2O4 (Example 1) showed the most significant covalent competition. At the same time, the electron distribution was improved, such as Figure 2 As shown, stronger covalent competition makes electrons enriched at the metal site, which is more conducive to the activation of ozone.

[0164] 2. Scanning electron microscope (SEM) detection

[0165] The materials of Examples 1 to 4 were subjected to scanning electron microscope (SEM) testing, and the test results are as follows: Figure 3 shown.

[0166] As can be seen from the figure, MnFe2O4, Cu 0.25 Mn 0.75 Fe2O4、Cu 0.5 Mn 0.5 Fe2O4、Cu 0.75 Mn 0.25 Fe2O4 presents a three-dimensional porous sponge shape with a large specific surface area and exposes more active sites.

[0167] 3. X-ray diffraction (XRD) test

[0168] The MnFe2O4 and Cu prepared in Examples 1 to 4 0.25 Mn 0.75 Fe2O4、Cu 0.5 Mn 0.5 Fe2O4、Cu 0.75 Mn 0.25 Fe2O4 material was subjected to X-ray diffraction analysis, and the obtained XRD spectrum was as follows Figure 4 As shown. MnFe2O4, Cu prepared in Examples 1 to 4 0.25 Mn 0.75 Fe2O4、Cu 0.5 Mn 0.5 Fe2O4、Cu 0.75 Mn 0.25The Fe2O4 materials all have similar diffraction peaks. Similar diffraction peaks at 18.3°, 30.2°, 35.6°, 43.2°, 57.1° and 62.8° are attributed to the (111), (220), (311), (400), (511) and (440) planes, respectively. All peaks are XRD characteristic peaks of MnFe2O4 or CuFe2O4, indicating that the synthesized materials have a typical spinel structure.

[0169] 4. Raman test

[0170] The materials prepared in 1 to 4 were subjected to Raman testing, such as Figure 5 As shown, MnFe2O4, Cu 0.25 Mn 0.75 Fe2O4、Cu 0.5 Mn 0.5 Fe2O4、Cu 0.75 Mn 0.25 Fe2O4 material has a peak at about 270 and 586 cm -1 There are two obvious peaks at 213 and 336 cm, corresponding to the A1g mode symmetric stretching vibration of Cu-O and Mn-O bonds, respectively. -1 The peaks observed at g and T 2g As the Cu content increases, the intensity of the Cu-O vibration gradually increases, while the intensity of the Mn-O vibration gradually decreases, proving that the introduction of Cu replaces Mn and integrates into the tetrahedral sites in the spinel structure. More significantly, compared with the material MnFe2O4 in Example 2, the Cu in Example 1 0.25 Mn 0.75 The Fe-O bond in Fe2O4 has a blue shift, indicating that the introduction of Cu enhances the covalency of the Fe-O bond. As the amount of Cu doping increases, the Fe-O bond gradually red shifts. The displacement change of the Mn-O peak also shows a similar trend. Therefore, Cu x Mn 1-x Fe2O4 presents a typical volcano-type covalent competition curve, in which the material Cu in Example 1 0.25 Mn 0.75 Fe2O4 exhibits the most significant covalent competition effect. The results are consistent with the previous theoretical calculation results.

[0171] 5. In-situ Raman testing

[0172] The material prepared in Example 1 was subjected to in-situ Raman testing. Figure 6 As shown, the activation of O3 on the catalyst surface was analyzed by in-situ Raman spectroscopy. As O3 continued to flow, the material of Example 1 was 0.25 Mn0.75 The Fe2O4 / O3 reaction system showed the presence of 827 and 932 cm -1 The two new characteristic peaks represent the generation of surface molecular oxygen (*O2, 1.35V) and surface atomic oxygen (*O, 2.43V), respectively. This indicates that the material in Example 1 activates ozone through bridge adsorption, directly adsorbing ozone on two sites, and then the ozone is disconnected to form surface molecular oxygen and surface atomic oxygen.

[0173] 5. Catalytic efficiency test

[0174] The performance test results of the above catalytic ozone oxidation degradation of methyl mercaptan are shown in Table 1.

[0175] Table 1 Test results of catalytic efficiency of multi-metal spinel oxides

[0176]

[0177]

[0178] As can be seen from Table 1, the catalytic efficiency of Cu-doped multi-metal spinel oxides (Examples 1 to 4) presents a volcano-shaped distribution. With the introduction of Cu, the catalytic efficiency first increases and then decreases. 0.25 Mn 0.75 Fe2O4 has the highest catalytic efficiency, and the performance ranking is as follows: Cu 0.25 Mn 0.75 Fe2O4>Cu 0.5 Mn 0.5 Fe2O4>Cu 0.75 Mn 0.25 Fe2O4>MnFe2O4.

[0179] Examples 1, 5, 6 and 7 test the moisture resistance of the material in Example 1 by changing the relative humidity of the air during the test reaction. The results show that the catalytic efficiency is the highest when the relative humidity is RH=40%, and it also shows good catalytic efficiency when the high humidity is RH=70%, indicating that the catalyst has strong adaptability to environmental humidity. 0.25 Mn 0.75 The dosage of Fe2O4 is 0.25 Mn 0.75 When the dosage of Fe2O4 is 3 mg, 100% of methyl mercaptan degradation can be achieved, showing an excellent catalytic effect. 0.25 Mn 0.75The long-term stability of Fe2O4 was tested, and it was found that when the dosage was 30 mg, methyl mercaptan was continuously degraded and the catalytic efficiency could be maintained at 80% for 24 hours, showing strong catalyst stability. 0.25 Mn 0.75 Fe2O4 material, from the results of catalytic efficiency, it can be concluded that the dosage of citric acid is 3.15g which is more suitable. A smaller dosage of citric acid will prevent the material from forming a porous sponge during the calcination process, and the material will be denser and have a smaller specific surface area. A larger dosage of citric acid will cause the porous structure of the material to collapse, and it is not conducive to forming a porous sponge that is easy to catalyze. Examples 1, 13 and 14 change the Cu 0.25 Mn 0.75 The calcination temperature of Fe2O4 material is used to obtain Cu 0.25 Mn 0.75 Fe2O4 material, the catalytic efficiency results show that the spinel phase is not easily formed at a lower calcination temperature, the catalytic efficiency is low, and the appropriate calcination temperature is about 400°C. Examples 1, 15 and 16 tested the catalytic efficiency of the material of Example 1 at different ozone flow rates by changing the ozone flow rate. A lower ozone flow rate is not conducive to the complete removal of organic gases, and a higher ozone flow rate is prone to ozone excess. The appropriate ozone flow rate is 3 to 20 mL / min.

[0180] The results of Example 1, Comparative Example 1 and Comparative Example 2 show that Cu 0.25 Mn 0.75 Fe2O4 material has a certain adsorption capacity for methyl mercaptan in air and nitrogen atmospheres, and can efficiently activate ozone to degrade methyl mercaptan in an ozone atmosphere.

[0181] Cu 0.25 Mn 0.75 The Fe2O4 material (Example 1) was compared with common ozone catalysts, including commercial MnO2 (Comparative Example 3) and MnFe2O4 (Comparative Example 4), as well as MnFe2O4 prepared by other inventive methods (Comparative Example 6). It was found that the material synthesis method of the present invention can be used to prepare an efficient ozone catalyst. Comparative Example 5 Co-doped MnFe2O4 material Co was prepared by the synthesis method of the present invention. 0.25 Mn 0.75 Fe2O4, whose catalytic efficiency is much lower than Cu 0.25 Mn 0.75 Fe2O4 material (Example 1). It shows that the Cu prepared by design 0.25 Mn 0.75Fe2O4 material has high catalytic activity, in which Fe-O-Mn forms a strong covalent competition and activates ozone through bridge adsorption, and the Cu site is mainly used to adsorb methyl mercaptan.

[0182] 6. Density functional theory calculations

[0183] The active reaction sites of the catalyst were calculated by density functional theory calculations, such as Figure 7 As shown, Cu 0.25 Mn 0.75 The bridge adsorption strength of Fe2O4 material for ozone is higher than that of linear adsorption, indicating that the designed Cu 0.25 Mn 0.75 Fe2O4 material has the function of bridge-type adsorption of ozone. 0.25 Mn 0.75 The Fe-O-Mn in the Fe2O4 material forms a strong covalent competition, which can enhance the bridge adsorption activation of ozone. At the same time, Cu has a strong adsorption effect on methyl mercaptan and becomes the main adsorption site of methyl mercaptan. Based on this, the material designed and prepared by the present invention becomes a functional catalytic material.

[0184] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for treating organic gas pollution by catalytic ozone oxidation, characterized in that: The following steps are involved: The catalyst was placed in a continuous flow microreactor with an ozone flow rate of 3 to 30 mL / min and organic gas introduced; Wherein, the catalyst is a medium entropy spinel oxide catalyst, Cu x Mn 1-x Fe2O4, x=0-0.75; the organic gas is a sulfur-containing organic volatile gas.

2. The method according to claim 1, characterized in that The sulfur-containing organic volatile gas is selected from one or more of methyl mercaptan, ethyl mercaptan, methyl sulfide, dimethyl disulfide or carbon sulfide.

3. The method according to claim 1, characterized in that The inlet humidity of the continuous flow microreactor is 0% to 70%.

4. The method according to claim 1, characterized in that: The ozone is generated by an ozone generator, and the flow rate is controlled by a mass flow meter.

5. The method according to claim 1, characterized in that The concentration of the ozone is 500-1000 ppm.

6. The method according to claim 1, characterized in that The sulfur-containing organic volatile gas is used at a concentration of 40 to 60 ppm.

7. The method according to claim 1, characterized in that The preparation method of the catalyst comprises the following steps: S1. Mix one or more metal salts of Cu, Fe or Mn and citric acid in a predetermined ratio and grind evenly; S2. The mixture is placed in an air atmosphere and calcined at 300-500° C. for 1.5-2.5 h to obtain a medium-entropy spinel oxide catalyst.

8. The method according to claim 7, characterized in that The catalyst is Cu x Mn 1-x Fe2O4, x=0, 0.25, 0.5, 0.

75.

9. The method according to claim 7, characterized in that: The metal salt is a nitric acid or acetate metal salt.

10. Use of the method for treating organic gas pollution by catalytic ozone oxidation as claimed in any one of claims 1 to 9 in the field of air pollution control.